Communication as a tool of humanization of nursing care: experiences in intensive care unit - Barlem, Edison Luiz Devos (2017)
The present study appears up to the questioning involving the relevance of the communication as instrument to humanizing the nursing care at the Intensive Therapy Unit (ITU). The objective is to know how the patients noticed the communication process implemented by the nursing staff into that ambient and identifying which are their perceptions about the received cares done by the nursing staff and lived situations at that ambient related to the communication process settled down by the nursing staff. So that, it was done a qualitative research through semi-structured interview with seven patients that were into at the general ITU of an university hospital the extreme south of Rio Grande do Sul, from January 2004 to June 2006, about aspects referents to the received cares with special attention to the communication process. The age of respondents ranged from 21 to 73 years. After reviewing the speech, there were two categories: the experience in the ITU, their meanings and the needs of communication and ITU: potential environment of care.The present results permitted to conclue that the most of the customers consider that the recived care at the ITU were satisfactory and recognizing that the nursing staff worries trying to attempt of communicating with the patient, and suppling a good value for looking, presence and touching.